Screening for Harassment, Abuse, and Discrimination among Surgery Residents: An EAST Multicenter Trial. Issue 5 (May 2019) - Fitzgerald, Caitlin A.; Smith, Randi N.; Luo-Owen, Xian; Turay, David; Ferrada, Paula; Han, Jinfeng; Williams, Brian H.; Hussain, Munira; Ekeh, A. Peter; Herzing, Karen; Zakrison, Tanyal; Gelbard, Rondib
Estimating the prevalence of harassment, verbal abuse, and discrimination among residents is difficult as events are often under-reported. The purpose of this study was to determine the prevalence of discrimination and abuse among surgical residents using the HITS (Hurt, Insulted, Threatened with harm or Screamed at) screening tool. A multicenter, cross-sectional, survey-based study was conducted at five academic teaching hospitals. Of 310 residents, 76 (24.5%) completed the survey. The HITS screening tool was positive in 3.9 per cent. The most common forms of abuse included sexual harassment (28.9%), discrimination based on gender (15.7%), and discrimination based on ethnicity (7.9%). There was a positive correlation between individuals who reported gender discrimination and racial discrimination (r = 0.778, n = 13, P = 0.002). Individuals who experienced insults were more likely to experience physical threats (r = 0.437, n = 79, P < 0.001) or verbal abuse (r = 0.690, n = 79, P < 0.001). Discrimination and harassment among surgical residents in academic teaching hospitals across the United States is not uncommon. Further research is needed to determine the impact of these findings on resident attrition.